Believing in an Otherwise: Studying Religion as Spiritual Activism - Robathan, Lucie (Arc, 2023)
This paper will propose that Gloria Anzaldúa’s “spiritual activism,” as a praxis wrought through the confluence of the spiritual and the political, could also be a model for embarking upon the study of religion differently. Walter Mignolo emphasizes that to understand what it means to decolonize requires specificity, through “looking at other W questions: Who is doing it, where, why, and how?” I shall suggest that spiritual activism as a decolonial framework demands that scholars of religion ask themselves, in turn, what they believe.